2007
DOI: 10.2981/0909-6396(2007)13[52:ewggps]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Estimating wolverineGulo gulopopulation size using quadrat sampling of tracks in snow

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…The WEAR population covers an area of approximately 100,000 km 2 . Although population density for this area is unknown, Golden et al (2007b) reported densities of approximately 10 animals/1,000 km 2 for a Canadian population in a similar environment, which would give an approximate population of 1,000 animals in our area. However, because this estimate is highly uncertain, we used a conservative range of 300-1,500 individuals, which reflects a realistic range of animals within the area.…”
Section: Population Model and Model Parametersmentioning
confidence: 84%
“…The WEAR population covers an area of approximately 100,000 km 2 . Although population density for this area is unknown, Golden et al (2007b) reported densities of approximately 10 animals/1,000 km 2 for a Canadian population in a similar environment, which would give an approximate population of 1,000 animals in our area. However, because this estimate is highly uncertain, we used a conservative range of 300-1,500 individuals, which reflects a realistic range of animals within the area.…”
Section: Population Model and Model Parametersmentioning
confidence: 84%
“…This facultative scavenger occupies a cold, low-productivity niche (Copeland et al, 2010;Inman et al, 2012a,b) that results in sparse population densities ($5/1000 km 2 ) and low reproductive rates (0.7 young/female > 3 yrs/yr) across its range (Golden et al, 2007;Inman et al, 2012a;Persson et al, 2006). As a result, wolverine populations are relatively vulnerable due to their small size and limited capacity for growth (Brøseth et al, 2010;Persson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…(), we found that modelling spatial correlation between adjacent trail segments increased occupancy estimates and failing to account for the spatial correlation would result in negatively biased occupancy estimates with increased type I error associated with narrow CIs. Given the prevalence of winter snow‐based tracking studies in monitoring (Stephens et al ., ; Golden et al ., ; Linnell et al ., ; Magoun et al ., ; Gardner et al ., ; Aing et al ., ; Webb & Merrill, ), spatially and temporally replicated occupancy surveys are a promising monitoring technique.…”
Section: Discussionmentioning
confidence: 99%
“…Snow‐tracking surveys have been used extensively to estimate species distribution and relative abundance using both ground (Thompson et al ., ; Stanley & Bart, ; Hayward et al ., ; Stephens et al ., ; Linnell et al ., ) and aerial‐based surveys (Becker, Spindler & Osborne, ; Golden et al ., ; Magoun et al ., ; Gardner et al ., ; Aing et al ., ; Webb & Merrill, ). Aerial surveys usually focus upon single species within open landscapes, whereas ground surveys detect multiple species within both open and forested landscapes.…”
Section: Introductionmentioning
confidence: 98%